Nutritional Recovery Promotes Hypothalamic Inflammation in Rats during Adulthood - Silva, Hellen Barbosa Farias; de Almeida, Ana Paula Carli; Cardoso, Katarine Barbosa; Ignacio-Souza, Letícia Martins; Reis, Silvia Regina de Lima; Reis, Marise Auxiliadora de Barros; Latorraca, Márcia Queiroz; Milanski, Marciane; Arantes, Vanessa Cristina (Mediators of Inflammation, 2014)
We evaluated whether protein restriction in fetal life alters food intake and glucose homeostasis in adulthood by interfering with insulin signal transduction through proinflammatory mechanisms in the hypothalamus and peripheral tissues. Rats were divided into the following: a control group (C); a recovered group (R); and a low protein (LP) group. Relative food intake was greater and serum leptin was diminished in LP and R compared to C rats. Proinflammatory genes and POMC mRNA were upregulated in the hypothalamus of R group. Hypothalamic NPY mRNA expression was greater but AKT phosphorylation was diminished in the LP than in the C rats. In muscle, AKT phosphorylation was higher in restricted than in control animals. The HOMA-IR was decreased in R and C compared to the LP group. In contrast, the Kitt in R was similar to that in C and both were lower than LP rats. Thus, nutritional recovery did not alter glucose homeostasis but produced middle hyperphagia, possibly due to increased anorexigenic neuropeptide expression that counteracted the hypothalamic inflammatory process. In long term protein deprived rats, hyperphagia most likely resulted from increased orexigenic neuropeptide expression, and glucose homeostasis was maintained, at least in part, at the expense of increased muscle insulin sensitivity.